Satow's diplomatic practice - Roberts, Ivor; Satow, Ernest Mason (Oxford University Press, 2018)
An indispensable guide for anyone working in or studying the field of diplomacy, this seventh, centenary edition of Satow's Diplomatic Practice provides a comprehensive overview and analysis of all areas of diplomacy and diplomatic practice.